2005
DOI: 10.1002/cmr.b.20043
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed saturation recovery 250 MHz electron paramagnetic resonance spectrometer

Abstract: Pulsed saturation recovery capability has been added to the pulsed 250 MHz EPR spectrometer previously described. The design of the spectrometer is sufficiently flexible so that the only change needed was an interchangeable plug-in card that directed the VHF pulses and the low-power CW VHF to monitor the spin recovery following saturation. The plug-in module converts the ESE spectrometer to a SR spectrometer. The switch in the plug-in module for pulsed ESE or FID operation with the crossed-loop resonator (CLR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…A 16-pulse phase cycling sequence was used to minimize the impact of the FID on the spin echo decays. Room-temperature values of T 1 and T 2 also were measured on locally constructed spectrometers operating at 2.76, 1.9, and 0.25 GHz . Phase cycling and a magnetic object in the magnetic field (or a field gradient) were used to minimize the impact of the FID.…”
Section: Methodsmentioning
confidence: 99%
“…A 16-pulse phase cycling sequence was used to minimize the impact of the FID on the spin echo decays. Room-temperature values of T 1 and T 2 also were measured on locally constructed spectrometers operating at 2.76, 1.9, and 0.25 GHz . Phase cycling and a magnetic object in the magnetic field (or a field gradient) were used to minimize the impact of the FID.…”
Section: Methodsmentioning
confidence: 99%
“…9,10 Purpose-built saturation recovery spectrometers have been reported by Quine et al, 11 Beck et al, 12 and Mailer et al 13 at X-band and by Quine et al at L-band 14 and 250 MHz. 15 Saturation recovery is available as an option for the Bruker Elexsys E580 spectrometer that uses an electron-electron double resonance (ELDOR) accessory and a 5 W solid state amplifier. Recently, digital components such as arbitrary waveform generators (AWG) and fast digitizers have made it possible to re-envision continuous wave saturation recovery spectrometers.…”
Section: Articlementioning
confidence: 99%
“…Initially, Abs and Abs D signals measured with our locally designed and built 250MHz spectrometer [15] had different amplitudes. Careful analysis of the electrical circuit responsible for phase-sensitive detection (see Fig.1) revealed that the 90° splitter (right hand side of Fig.…”
Section: Instrumental Considerationmentioning
confidence: 99%